The Effect of Baby Massage on Improvement Baby Weight - Nurul Fatmawati; Yesvi Zulfiana; Yopi Suryatim Pratiwi (Journal for Quality in Public Health, 2021)
The problem experienced by toddlers is that growth disorders in Indonesia have started to emerge from children aged 1-6 months, so that efforts are needed to reduce the rate of growth disorders or to or to increase weight presentation. Increasing body weight is an indicator of infant health that can be used as a benchmark for infant growth. Body weight is the most important anthropometric measure and is most often used in newborns (neonates). One of the treatments that can be done to increase body weight is by giving massage to babies. Baby massage can stimulate the penvernaan hormones insulin and gaselin, so that food absorption becomes better. This causes babies to feel hungry quickly so they eat more often and gain weight. The purpose of this study was to determine the effect of infant massage on infant weight gain. The method in this study is a literature review, which tries to explore how the effect of infant massage on infant weight gain. The results in this study indicate that the results of 6 previous studies indicate that there is a significant effect of infant massage on the increase in infant body weight. The conclusion in this study is that massage in infants can increase the baby's weight. This is because the massage that is carried out regularly on babies is used to massage the legs, stomach, chest, hands, back, and stretching movements can increase the baby's weight. The massage will cause nerve action potential that stimulates the vagus nerve.